2011
DOI: 10.1038/nature09868
|View full text |Cite
|
Sign up to set email alerts
|

Distinct representations of olfactory information in different cortical centres

Abstract: Sensory information is transmitted to the brain where it must be processed to translate stimulus features into appropriate behavioral output. In the olfactory system, distributed neural activity in the nose is converted into a segregated map in the olfactory bulb. In this study we ask how this ordered representation is transformed in higher olfactory centers. We have developed a tracing strategy to define the neural circuits that convey information from individual glomeruli in the olfactory bulb to the pirifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
403
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(451 citation statements)
references
References 30 publications
(28 reference statements)
20
403
0
3
Order By: Relevance
“…In all the three species, individual output neurons in the OB or the antennal lobe send axons to multiple brain areas. Each brain area appears to adopt one of two major strategies of projections to be received: (1) restricted and stereotyped projections with respect to glomerular classes for the fly lateral horn 14 , zebrafish Hb and mouse cortical amygdala 9,10 ; (2) broad and random projections for the fly mushroom body 49 , zebrafish pTel (Dp), and mouse piriform cortex 9,10 . Thus, our findings support the idea that the two distinct modes of connectivity patterns (stereotyped and random), which are suitable for innate and learned behaviours, are applicable to all animal species as a fundamental principle for olfactory representations in higher brain centres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all the three species, individual output neurons in the OB or the antennal lobe send axons to multiple brain areas. Each brain area appears to adopt one of two major strategies of projections to be received: (1) restricted and stereotyped projections with respect to glomerular classes for the fly lateral horn 14 , zebrafish Hb and mouse cortical amygdala 9,10 ; (2) broad and random projections for the fly mushroom body 49 , zebrafish pTel (Dp), and mouse piriform cortex 9,10 . Thus, our findings support the idea that the two distinct modes of connectivity patterns (stereotyped and random), which are suitable for innate and learned behaviours, are applicable to all animal species as a fundamental principle for olfactory representations in higher brain centres.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with an optical imaging study that found no apparent spatial organization of odour-evoked activity patterns in the piriform cortex 11 . In contrast, the anterior olfactory nucleus and the cortical amygdala receive topographic and biased projections from the OB, respectively 9,10 . Thus, a conceptual organization has been proposed in which the secondary olfactory pathway bifurcates to transform odour information into stereotyped and random representations, features suited for directing innate and learned behaviours, respectively 12,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The olfactory system presents other problems: OR projections segregate and project to receptor-specific glomeruli, but beyond the glomerulus, there is no obvious topography (11). The unpredictable variation in the number of OR genes across species is also mysterious.…”
Section: Convergence In Olfactory System Structure and Functionmentioning
confidence: 99%
“…Il est important de noter que la cellule internalisée est vivante au moment de l'entose et que la cellule hôte joue un rôle passif au cours de ce processus. Ce mécanisme d'internalisation homotypique contrôlé par les cadhérines permet de distinguer l'entose des autres processus de cannibalisme cellulaire [1][2][3]. Par la suite, la cellule internalisée est digérée lentement par les lysosomes de la cellule hôte dans la plupart des cas (Figure 2A).…”
Section: Quelles Conséquences Pour Le Codage De L'information Olfactiunclassified